The poetry of shell shock : wartime trauma and healing in Wilfred Owen, Ivor Gurney and Siegfried Sassoon / by Daniel Hipp. - Hipp, Daniel W. (McFarland & Co, 2005)
Summary: "This work investigates the ways in which the poetry of war functioned as a means for Owen, Gurney and Sassoon to express the inexpressible and to extract value out of the experience of war"--Provided by publisher